Factors Influencing The Food Security And Nutrition Expenditures In Farm Households In Punjab, Pakistan - Rose, Sobia; Ihsan, Asima; Adil, Shahid (European Scientific Journal, ESJ, 2021)
The study was designed to explore the preventive side of a healthy farming community which depends on better food intake and the patterns of food and its linkages with socio-economic status of the farmers in the province of Punjab. The aim of the study was to identify the important factors that contribute to poverty amongst the farm households. The study also determines the factors responsible for the nutritious food consumption patterns amongst the farm households. In order to find the important determinants of poverty amongst farmers, we have used the binary logistic regression. The results of the study revealed that education, family size, crops diversification, time given to farm activity and farm size are significant factors in determining the poverty status of farming households. The results also depicted that small farmers spend fewer amounts on nutritious food items than big farmers. This study found a positive impact of diversified cropping patterns on food consumption amongst farmers. The level of education was also found to be significantly affecting the food consumption expenditures. The study recommended that pro-poor policies be implemented to increase labour productivity and improve food consumption among farmers. Educating farm families about the value of a healthy diet will help them make better food choices. Furthermore, the value of crop diversification must be recognized in order to lift farm households out of poverty and ensure their food security.